2023
DOI: 10.4166/kjg.2023.039
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of 7-day Tailored Therapy for Helicobacter pylori Eradication based on Clarithromycin Resistance

June Hwa Bae,
Hyeong Ho Jo,
Joong Goo Kwon
et al.

Abstract: Background/Aims: Increasing resistance to clarithromycin (CAM) of Helicobacter pylori (H. pylori) is one of the main causes of recent decrease in eradication rate of standard triple therapy. The aim of this study was to evaluate the usefulness of 7-day tailored therapy based on the existence of CAM resistance. Methods: From January 2017 to May 2022, a total of 481 consecutive patients with H. pylori infection were recruited in Daegu Catholic University Medical Center. Treatment regimen was selected based on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…Studies have reported better eradication success rates using tailored therapy than empiric therapy, especially when antimicrobial susceptibility testing was performed before treatment. 148 149 150 151 However, the benefit of tailored therapy has not been demonstrated in clinical trials comparing tailored therapy with empirical quadruple regimens as a first-line treatment or tailored therapy after previous treatment failure. 151 152 153 This suggests that the benefit of tailored therapy is not obvious when the empirical regimen is highly effective for H. pylori eradication.…”
Section: Cilnical Implication and Future Directionsmentioning
confidence: 99%
“…Studies have reported better eradication success rates using tailored therapy than empiric therapy, especially when antimicrobial susceptibility testing was performed before treatment. 148 149 150 151 However, the benefit of tailored therapy has not been demonstrated in clinical trials comparing tailored therapy with empirical quadruple regimens as a first-line treatment or tailored therapy after previous treatment failure. 151 152 153 This suggests that the benefit of tailored therapy is not obvious when the empirical regimen is highly effective for H. pylori eradication.…”
Section: Cilnical Implication and Future Directionsmentioning
confidence: 99%